Intravenous catheter-associated fungemia due to Candida rugosa. - Reinhardt, J F (1985)
We report a case of intravenous catheter-associated fungemia caused by Candida rugosa; this is the first report of such an infection in a human. Multiple cultures of blood taken over a 24-h period and of the intravenous catheter tip were positive for this unusual isolate. The patient was treated with intravenous amphotericin B and made an uneventful recovery. Intravenous cannulae and other intravascular devices are well recognized as potential sites of intravascular infection by a variety of microorganisms, including several Candida species; however, fungemia caused by C. rugosa has not been reported.